If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 = 6r + -24 + 3t Reorder the terms: 30 = -24 + 6r + 3t Solving 30 = -24 + 6r + 3t Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6r' to each side of the equation. 30 + -6r = -24 + 6r + -6r + 3t Combine like terms: 6r + -6r = 0 30 + -6r = -24 + 0 + 3t 30 + -6r = -24 + 3t Add '-30' to each side of the equation. 30 + -30 + -6r = -24 + -30 + 3t Combine like terms: 30 + -30 = 0 0 + -6r = -24 + -30 + 3t -6r = -24 + -30 + 3t Combine like terms: -24 + -30 = -54 -6r = -54 + 3t Divide each side by '-6'. r = 9 + -0.5t Simplifying r = 9 + -0.5t
| 7-(-5)+4-(-3)= | | 12=-2m | | -x-(1/7)=x+(1/6)+(2/7) | | 1/6x^2=48 | | 4w+13=61 | | x+2(x-4)=100 | | 1/3x^2=48 | | (275)(x-373)(.444)=(100)(x-295)(4.184) | | 1/3x^2=54 | | Y=3/2*0-6 | | -.25x+6x-2=20 | | 8/x+8=7/x-4 | | 7t^2+3=10t | | 0.18(y-8)+0.14y=0.16y-0.05(60) | | (3/9)+(x/3)=7/9 | | 10-(3x-4)=8-4x | | (x^2)-2x-48=0 | | -10.4x^2+132x+332=750 | | -3(x-7)-6(3x-3)=-22(x-1)+9 | | (x^3)-4(x^2)-9x+36=0 | | x-(-5)=-5 | | (5x^2)-15x-90=0 | | -3p^2+17p=0 | | 8(x-4)+7=-25 | | 6q+24+6q-3=33 | | -7a^2+2d+9=0 | | 6x+5=7+5 | | 2-5/2b=2b/b+1 | | 2x+2=-x-4 | | 2x^3+16x^2+14x=0 | | 4x^2/(600-x)(600-x) | | 1/8=6/7x-1/6 |